Calumenin contributes to ER-Ca2+ homeostasis in bronchial epithelial cells expressing WT and F508del mutated CFTR and to F508del-CFTR retention. (March 2017) - Philippe, Réginald; Antigny, Fabrice; Buscaglia, Paul; Norez, Caroline; Huguet, Florentin; Castelbou, Cyril; Trouvé, Pascal; Becq, Frédéric; Frieden, Maud; Férec, Claude; Mignen, Olivier
Graphical abstract: Highlights: Calumenin expression modulates SERCA pump activity in non-CF and CF bronchial epithelial cells. Modulating Calumenin expression changes ER-Ca 2+ concentration in bronchial epithelial cells. Calumenin knockdown restores a CFTR activity in F508del-CFTR expressing cells. Abstract: Cystic Fibrosis (CF) is the most frequent fatal genetic disease in Caucasian populations. Mutations in the chloride channel CF Transmembrane Conductance Regulator ( CFTR ) gene are responsible for functional defects of the protein and multiple associated dysregulations. The most common mutation in patients with CF, F508del-CFTR, causes defective CFTR protein folding. Thus minimal levels of the receptor are expressed at the cell surface as the mutated CFTR is retained in the endoplasmic reticulum (ER) where it correlates with defective calcium (Ca 2+ ) homeostasis. In this study, we discovered that the Ca 2+ binding protein Calumenin (CALU) is a key regulator in the maintenance of ER-Ca 2+ calcium homeostasis in both wild type and F508del-CFTR expressing cells. Calumenin modulates SERCA pump activity without drastically affecting ER-Ca 2+ concentration. In addition, reducing Calumenin expression in CF cells results in a partial restoration of CFTR activity, highlighting a potential function of Calumenin in CFTR maturation. These findings demonstrate a pivotal role for Calumenin in CF cells, providing insights into how modulation of Calumenin expression or activity may be used as a potential therapeutic tool to correct defects in F508del-CFTR.